MENGGALI ‘ILLAT HUKUM PERBEDAAN AGAMA SEBAGAI HALANGAN WARIS (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2016)
Kompilasi Hukum Islam does not regulate interfaith inheritance distinctly. It only requires the testator and the heirs have the same religion. At court, judges of religious courts employ obligatory bequest (waá¹£iat wÄjibah) to divide inheritance to non-Muslim heirs, based on jurisprudence of the Supreme Court Number 368 K/AG/1995. As the result, different faith still become hindrance for Muslim and non-Muslim to inherit each other due to law enforcement without considering the legal reasoning (ratio legis) of the law. In this case, it is important to investigate the legal reason (ratio legis) of the hadith that prohibits the interfaith inheritance as this article tries to do. To do the investigation, the author employs Islamic legal theories (uá¹£Å«l fikih) and hermeneutics approach. As the result, the author comes to the conclusion that the ratio legis of the hadith that prohibits the interfaith inheritance is due to hostility and crime element and not due to different faith. Keywords: Interfaith Inheritance, Ratio Legis, Equality